Effects of carbohydrates on brain tryptophan availability and stress performance - Markus, C.R. (Biological psychology, 2007)
Although glucose intake has been associated with enhanced mental performance, this does not follow a clear synchronized relationship and findings are inconsistent. Given the brain's need for glucose during demanding conditions, glucose intake may be beneficial for stress performance. Brain serotonin may be involved as a postprandial mechanism initiated by increases in plasma tryptophan to the sum of the other large neutral amino acids (Trp/LNAA ratio). We tested whether carbohydrate drinks compared to placebo drinks increase the plasma Trp/LNAA ratio and improve stress performance and mood. Thirty-seven healthy subjects were monitored in a double-blind placebo-controlled study for performance when continuously exposed to cold pressor stress; 2 h after carbohydrate- or placebo-intake. Cold pressor stress significantly increased cortisol and reduced mood and cognitive performance, whereas carbohydrates significantly increased plasma Trp/LNAA and positively influenced performance and mood under stress.